Morphometric Assessment of the Piriform Aperture and Its Clinical and Forensic Applications - Beryl Shitandi Ominde; Joyce Ekeme Ikubor; Jennifer Efe Jaiyeoba-Ojigho; Orovwoghene Faithful Omoro; Patrick Sunday Igbigbi (Mustansiriya Medical Journal)
Background: The piriform aperture (PA) is a midface structure that forms the anterior skeletal boundary of the nose. It is highly variant due to its physiological adaptations to the climate. Its variations are useful in forensic identification and reconstructive surgeries of the face. This study aimed at determining the PA’s dimensions and their accuracy in sex determination. Materials and Methods: The PA’s dimensions were retrospectively examined using 336 (199 males and 137 females) adult cranial computed tomography images in the database of the radiology unit of a university teaching hospital in Delta State, Nigeria, following institutional authorization. The aperture’s index was calculated as a ratio of height to width. The data were analyzed using Statistical Package for the Social Sciences Version 23. The sexual dimorphism in the parameters was assessed using an independent t-test. Association among the continuous variables was analyzed by Pearson’s correlation test. P = 0.05 was considered statistically significant. The percentage accuracy for correct sex prediction was assessed using the discriminant function analysis. Results: A significant relationship between dimensions with sex was observed (P < 0.05). The width of the aperture was the best sex-discriminating parameter (70.2%). The overall accuracy for sex discrimination using the aperture’s dimensions was 75.0%. Conclusion: This study provides the standard ranges for the PA’s width and height, valuable for surgical planning. These dimensions were sexually dimorphic and demonstrated an acceptable overall accuracy of correct sex allocation (75%). Consequently, this aperture may be utilized as a supplementary tool in conjunction with other methods for sex determination within studied population.